Tailored light emission from color centers in nanodiamond using self-assembled photonic crystals - Sharma, Sachin; Ashish,; Nair, Rajesh V. (Frontiers in Nanotechnology, 2022)
The defect centers in solid-state materials especially the nitrogen-vacancy (NV) centers in diamond have shown a tremendous potential for their utilization in quantum technology applications. However, they exhibit certain drawbacks like the feeble zero phonon line with huge phonon contribution and the higher lifetime values. Here, we present a novel approach to control the spontaneous emission from NV centers in nanodiamond using engineered self-assembled photonic crystals. Using two complimentary emission measuring geometries at room temperature, we show a 63% suppression and 17% enhancement of NV center emission intensity using photonic stop gap, supported with simulations. The emission rates are modified in a broad spectral range of NV center emission and are consistent with Barnett-Loudon sum rule. The results are crucial for emerging quantum technologies using NV centers in diamond.